Massive duodenal ulcer bleeding due to the ruptured hepatic artery pseudoaneurysm after living donor liver transplantation - Masashi Kadohisa; Yukihiro Inomata; Masataka Sakisaka; Yasuhiko Sugawara; Taizo Hibi (Surgical Case Reports)
Abstract Background The rupture of a hepatic artery pseudoaneurysm (HAP) is a rare but lethal complication after living donor liver transplantation (LDLT) and often manifests as acute gastrointestinal bleeding. Case presentation This report describes three patients who experienced HAP after LDLT. These patients initially presented with active bleeding of a duodenal ulcer (DU) in the duodenal bulb, followed by diagnosis of the ruptured HAP by angiography. None of the patients had evidence of an active intra-abdominal infection or bile leakage preceding the rupture of HAP. All patients were initially treated by transcatheter arterial coil embolization (TAE). In all cases, TAE was successful for hemostasis but resulted in complete obstruction of the arterial inflow to the graft. Arterial revascularization by surgical reconstruction using the autologous arterial graft in one case and re-LDLT in another one was successfully performed. The other one succumbed to sepsis caused by later liver abscesses. Conclusion This is the first detailed case series of massive DU bleeding as a warning signal of ruptured HAP after LDLT. HAP should be included in the differential diagnosis when an LDLT recipient presents with gastrointestinal bleeding.